The Role of University Crown Foundations in Higher Education Policy: A Cross-Canada Study (1984–1998) - Thomarat, Jacqueline (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
This qualitative case investigation considers the historical, inter-provincial proliferation of university Crown foundations across Canada from 1984 to 1998. From the findings of over 40 interviews conducted between 2014 and 2017 and document analysis, this study uses a conceptual framework of policy entrepreneurship and institutionalism to provide evidence of Crown foundations’ policy engagement in post-secondary education and fiscal policy in Canada. The efforts to increase the availability of tax incentives to the system by policy entrepreneurs increased resources available to Canadian university Crown foundations, although the advantage to universities was only temporary.